Design and Implementation of Bluetooth Low Energy Based Access Control System - Sasongko, Arif; Prastya, Sidartha; Brillianshah, Elkhan Julian; Taruna, Muhamad; Hakim, Abdul (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
This paper discusses the design of a Bluetooth Low Energy (BLE) based access control system intended to make access control more practical to implement on areas with high personnel turnover rate by making access rules easy to set and making access keys relatively safe to distribute compared to existing key-based access control systems. The use of BLE technology allows the system to estimate key position within the system by utilizing the curve fitting method for distance estimation and the trilateral method for positioning. The proposed system consists of a server, an admin panel, electronic locks, access keys in the form of a wearable, and access keys in the form of an Android application. The system is found to be capable of implementing access control functionalities and capable of implementing indoor positioning based on sections.